Mycophenolato mofetil vs mycophenolate sodium after simultaneous pancreas- kidney transplantation (SPKT) - Rangel, Erika Bevilaqua (2009)
Purpose: Adverse gastrointestinal events are frequent after the use of Mycophenolate. The purposes of the present study were to report the incidence of acute non-infectious diarrhea, to determine the risk factors, and make a comparison on the severity between Mycophenolate Mofetil (MMF) and Enteric-Coated Mycophenolate Sodium (EC-MPS) after simultaneous pancreas-kidney transplantation (SPKT). Methods: It was included 165 SPKT patients from Dec/00 to May/07. Uni-and multivariate analyses were performed, being acute non- infectious diarrhea the dependent variable. P < 0.05 was significant. Results: Mean age, duration of dialysis and diabetes were 34.9 ± 8.2 years, 27.3 ± 18.3 months and 21.9 ± 16.2 years, respectively. 63% used MMF, 36.4% used EC-MPS, and 0.6% used Azathioprine. Multivariate analysis showed that the duration of diabetes (P = 0.049, CI 95% 1.0-1.13) and the use of MMF (P = 0.013, CI 95% 0.2-0.82) were the major determinants to post-SPKT acute diarrhea. Dose reduction of MMF (79.2% vs 62.3%, P = 0.024) and the severity of diarrhea associated to orthostatic hypotension were more pronounced with MMF than with EC-MPS (42.4% vs 15.1%, P = 0.001). There was no difference between MMF and EC-MPS after the dose reduction related to the occurrence of acute kidney rejection (30.8% vs 26.7%, P = 0.53). Conclusions: Post-SPKT acute non-infectious diarrhea is related to the duration of diabetes and to MMF. The preferential use of EC-MPS is associated to a lower need of dose reduction and less severe episodes of acute diarrhea compared to MMF, although the dose reduction was equally associated to acute kidney rejection.